Television and National Identity: An Ethnography of Television Audience in the Border of Indonesia-Malaysia - Rizki Briandana (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2019)
Television has a strategic position in constructing national identity. As part of the everyday life of the community, television provides a community-driven medium to construct its identity. In relation to the existence of mass media in the community and the issue of forming a national identity, there are unique problems that exist in the Sebatik Island of the Indonesian and Malaysian frontiers. These Indonesian people have no access to the broadcasting media, especially television, from Indonesia. This situation has persisted for several years, so the citizens of Sebatik Island use television broadcasts from Malaysia as their primary source of media communication. This study aims to examine how the people of Sebatik Island construct their national identity through the Malaysian television programs they watch daily. The methodology used in this study is ethnography with data collection techniques through observation and interviews of eight informants in September 2017. The result shows that the “mixed national identity” of Sebatik society is influenced by various factors and one of them is Malaysian television. Malaysian television programs also play a role as a socialization agent, among with other agents such as the presence of the community, the country, the organization, the culture, and the ideology.